Depression, anxiety and its predictor among internally displaced person in metekel Ethiopia, 2023: using a structural equation model - Bekeko, Solomon Debela; Nimani, Teshome Demis; Darcho, Samuel Demissie; Bayisa, Feyisa Shasho (Frontiers in Psychiatry, 2025)
IntroductionThese individuals face psychological and physical trauma, loss of jobs, and emotional isolation, which may lead to the development of depression and anxiety. In 2022, 120 countries had over 71 million IDPs, a 20% increase from the previous year. In sub-Saharan Africa, natural disasters accounted for 40% of all new IDPs worldwide.MethodAn institutional-based cross-sectional study was conducted in Ethiopia. A systematic random sampling method was used to select 997 respondents. Data were collected using a structured interview questionnaire. STATA Version 17 and Amos Version 21 were used for the analysis. Descriptive statistics were summarized using frequency, percentage, table, graph, chart, figure, and summary statistics. Structural equation modeling was employed to assess the relationship.ResultThe overall prevalence of depression and anxiety was 79.64% (95% CI: 77.02 82.03) and 74.62% (95% CI =71.83%, 77.23%) respectively. age (adjusted β = 0.0034, 95% CI: 0.0012, 0.0056), history of the death of a loved one (adjusted β = 0.132, 95% CI: 0.0803, 0.185), had formal education (β = -0.164, 95% CI: -0.229, -0.098) occupation other (adjusted β = -0.183, 95% CI: -0.261, -0.105), Not having medically confirmed mental illness (adjusted β = -0.185, 95% CI: (-0.325, -0.045), PTSD score (adjusted β = 0.0082, 95% CI: 0.0048, 0.012) associated with anxiety.ConclusionDisplacement medically confirmed mental illness, death of a loved one, and post-traumatic stress disorder (PTSD) significantly impact anxiety. Policymakers should provide greater access to mental health management and prevention services, and medical practitioners should understand the connection between depression and anxiety.